The Graduate - Webb, Charles (Penguin Group, 1963)
For twenty-one years I have been shuffling back and forth between classrooms and libraries. Now you tell me what the hell it's got me.' That's how Benjamin Braddock talked when he came down from university. Somehow it didn't seem to be what his father expected from a college education. And everyone was really appalled when Ben raped Mrs Robinson (that was her story anyway) and ran off with her daughter in the middle of her wedding to someone else...
Keywords: Fiction